Clinical factors associated with syphilis concordance in men in sexual partnerships: a cross-sectional couples study. (30th November 2017) - Towns, Janet M; Huffam, Sarah; Chow, Eric P F; Denham, Ian; Zhang, Lei; Ryan, Andrea; Bellhouse, Clare Elizabeth; Bissessor, Melanie; Bradshaw, Catriona S; Phillips, Tiffany; Graves, Stephen; Fairley, Christopher K; et al.
Abstract : Background: Syphilis infections continue to increase among men who have sex with men (MSM) in many countries, with rates often higher among HIV-positive MSM. There is limited understanding of the risk and determinants of syphilis transmission between men. We aimed to examine the concordance of early syphilis infection between male sexual partners and clinical factors associated with transmission. Methods: Men attending Melbourne Sexual Health Centre with their male partners, where at least one was diagnosed with early syphilis, were identified from linkage of partner records between March 2011 and April 2016. Early latent syphilis was defined as a new asymptomatic syphilis presentation of less than 2 years' duration. Associations between concordance and potential risk factors were examined using Fisher's exact test. Results: Among 43 couples (86 men) identified, there were 13 couples (26 men) where both were diagnosed with early syphilis, representing a concordance rate of 30.2% (95% CI 17.2% to 46.1%). Among the 13 concordant couples, 5 men had primary syphilis (4 penile, 1 anal), 11 secondary syphilis (8 generalised rash, 3 penile, 2 anal, 1 oral lesion) and 10 early latent infections. Concordance was higher among couples where at least one partner had secondary syphilis compared with couples where neither partner had secondary syphilis (53% (9/17) vs 15% (4/26), P=0.016). Furthermore, concordance was higher among couples where one was HIV positive compared with couples where both were HIV negative (62% (5/8) vs 23% (8/35), P=0.042). Conclusions: There was an overall concordance rate of 30%. Higher concordance rates for early syphilis infection between male sexual partners were associated with HIV and secondary syphilis.